2021
DOI: 10.1111/tbed.14267
|View full text |Cite
|
Sign up to set email alerts
|

Development and application of an indirect ELISA for the detection of antibody to porcine circovirus 4 in pigs

Abstract: Porcine circovirus type 4 (PCV4) was first reported in 2019 in China. So far, the viral DNA was detected from both healthy and diseased pigs in China and South Korea by using molecular techniques including PCR and real-time PCR. In contrast, a serological survey regarding the presence of PCV4 antibodies in the pig population was seldomly reported. In the present study, we describe the development of an indirect enzymelinked immunosorbent assay (ELISA) based on capsid protein for the detection of PCV4 antibodie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…Since GyH1 lacks a cell culture propagation system, PCR has been used as a method to detect GyH1 infection. Since the capsid proteins of some single-stranded circular DNA virus, such as duck circovirus [ 21 ], porcine circovirus [ 22 , 23 ], and chicken anemia virus [ 24 ], may induce antibody responses during viral infection, recombinant capsid protein-based serological tests should be useful tool for epidemiological investigations. VP1 is the major capsid protein abundantly produced during GyH1 infection, with high immunogenicity and stability [ 18 – 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since GyH1 lacks a cell culture propagation system, PCR has been used as a method to detect GyH1 infection. Since the capsid proteins of some single-stranded circular DNA virus, such as duck circovirus [ 21 ], porcine circovirus [ 22 , 23 ], and chicken anemia virus [ 24 ], may induce antibody responses during viral infection, recombinant capsid protein-based serological tests should be useful tool for epidemiological investigations. VP1 is the major capsid protein abundantly produced during GyH1 infection, with high immunogenicity and stability [ 18 – 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we developed an indirect ELISA using the GyH1 viral capsid protein as the coating antigen. ELISA assay can be used to detect specific antibody IgG of all GyH1 strains with sensitivity and specificity of 93.4% and 98.5%, respectively [ 21 23 ]. The results showed that the indirect ELISA has high sensitivity and specificity.…”
Section: Discussionmentioning
confidence: 99%
“…PCV4 Rep-specific antibodies were detected in sera from pigs of various ages, with the highest prevalence (67.8%) in sows, and the earliest evidence from a sample collected in 2008 [ 5 ]. In another serological survey of 1048 pig serum samples collected from Jiangsu province of China between 2018 and 2021, 3.44% of samples had PCV4 Cap-specific antibodies [ 27 ]. Although these serological studies provided insights into the prevalence of PCV4 in pigs, dynamics of viremia and antibody responses to PCV4 infections in swine herds require further investigation.…”
Section: Epidemiology Of Pcv4 and Clinical Diseases Associated With T...mentioning
confidence: 99%
“…As four distinct PCV are circulating in swine herds worldwide, exploring serologic cross-reactivity of PCV4 with other PCV is important to establish reliable serological diagnostic methods. Two studies demonstrated that the established PCV4 ELISA, based on Rep or Cap, had no serological cross-reactions with positive sera of other PCV [ 5 , 27 ]. Moreover, our previous study also demonstrated an absence of cross-reactions between PCV4 and either PCV2 or PCV3 [ 23 ].…”
Section: Future Perspectivesmentioning
confidence: 99%
“…The most recently reported PCV, namely, PCV4, was first identified in Chinese farmed pigs with severe clinical disease in 2019 [ 5 ]. Thereafter, several groups have conducted epidemiological investigations on PCV4 and found that PCV4 also exists widely in pigs [ 6 , 7 , 8 , 9 , 10 , 11 , 12 ]. Kim et al found that the positive rates of PCV4 in individual pig samples and at the farm level were 39.3% and 45.7%, respectively [ 9 ].…”
Section: Introductionmentioning
confidence: 99%